2022
DOI: 10.1021/acs.jpcc.2c05342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrophilic Thiol Ligands of Varying Denticity on the Luminescence Properties and Colloidal Stability of Quaternary Semiconductor Nanocrystals

Abstract: Binary photoluminescent semiconductor nanocrystals (quantum dots, QDs) are one of the best studied fluorescent nanomaterials, and their unique optoelectronic properties paved the road to many applications in (bio)nanophotonics, optoelectronics, and photovoltaics. However, concerns related to their toxic constituents like cadmium or lead and the emerging interest in greener chemistry synthesis approaches hamper their future applicability. Interesting alternatives for some applications like biosensing or bioimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Previously to obtaining AgInS QDs with emission in the NIR spectral range, partial substitution of silver ions in the lattice sites with copper ions, leading to narrowing of the PL band, was used, while the PL intensity was strongly reduced …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously to obtaining AgInS QDs with emission in the NIR spectral range, partial substitution of silver ions in the lattice sites with copper ions, leading to narrowing of the PL band, was used, while the PL intensity was strongly reduced …”
Section: Resultsmentioning
confidence: 99%
“…Indium-based ternary QDs, particularly CuInS(Se) and AgInS(Se), present an alternative to binary QDs due to their compositional and structural versatility and intense PL in the visible and NIR spectral range, which can be adjusted by QD composition, size, surface passivation, and ligand shell. In particular, CuInSe and AgInSe possessing a direct bandgap (1.04 and 1.24 eV) and a large Bohr exciton radius theoretically have great potential as NIR nanoprobes . However, there are only a few reports on the application of these ternary QDs in bioimaging.…”
Section: Introductionmentioning
confidence: 99%
“…In [50], the authors suggested that thiol groups could influence the PL emission p erties of aqueous I-III-VI QDs through the transfer of a hole to the redox level of sur Applying a numerical value of E LO equal to 36 meV obtained via Raman spectroscopy in [48,49], the authors of [27] determined the values of Γ inh and Γ LO to be 320 meV and 0.1 meV for the whole CuInS 2 QD stock ensemble. In our case, the values of Γ inh and Γ LO varied with fraction size in the ranges 245-280 meV and 80-110 meV, respectively.…”
Section: Temperature-dependent Photoluminescencementioning
confidence: 99%
“…In [50], the authors suggested that thiol groups could influence the PL emission properties of aqueous I-III-VI QDs through the transfer of a hole to the redox level of surface-bound disulfides formed via ligand oxidation. In our previous work [21], though, we observed very little narrowing of the PL curve with decreasing temperature for non-thiol (thiol-less) PVP-capped AgInS 2 QDs.…”
Section: Temperature-dependent Photoluminescencementioning
confidence: 99%
“…[10][11][12][13] Moreover, it has also been reported that the dispersibility and emission properties of NCs are altered by changing the primary, secondary, and tertiary structures of the phosphonic acids and thiols. 14 However, there are few examples that reveal the effect of the molecular structure of alkyl ligands on the excited-state dynamics of NCs. Revealing the correlation between the molecular structure of organic ligands and photophysical properties is important for the synthesis of NCs and allows arbitrary control of dispersion and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%